(untitled) (Orthodontic Journal of Nepal, 2022)
Introduction: With increase in number of adult orthodontic patients, the orthodontic- endodontic related patients are also expected to rise. There are number of clinical dilemma where both the specialties need robust guideline for clinical decision making. The effect of orthodontic force is expressed in different way in different patients and teeth which need to be understood by clinicians. On the contrary, the tooth movement of endodontically involved teeth demands careful evaluation of the tooth and its surrounding tissue, quality of root treatment, presence or absence of peri-apical pathologies, previous history of trauma etc. Management of external apical root resorption following orthodontic therapy might be challenging some time. Orthodontic extrusion of fractured teeth is one of the viable prosthetic rehabilitation options where orthodontic, endodontic and prosthodontics specialties are involved. So this review article will focus on reviewing current level of evidence on orthodontic- endodontic interface.